Macroprudential Instruments to Minimize the Financing Risk of Islamic Commercial Banks in Indonesia - Kurniawan S., Amri Darma; Sakuntala, Dwita; Zulfa, Andria; Nasution, Lia Nazliana (LPPM UIKA Bogor, 2024)
Bank Indonesia has established macroprudential policy as one of its strategies within the policy mix, utilizing various instruments to support the intermediation function and manage credit or financing risks. This research aims to investigate the impact of the countercyclical capital buffer, financing to funding ratio, and capital adequacy ratio on the non-performing financing ratio at Islamic commercial banks in Indonesia. The study employs a quantitative approach focusing on 13 Islamic commercial banks registered with the Otoritas Jasa Keuangan (Financial Services Authority). Secondary data covering a 6-month period from 2014 to 2023 is utilized for analysis. The research applies the multiple linear regression model using the Ordinary Least Square method. The simultaneous test (F-test) result indicate that the countercyclical capital Buffer, financing to funding ratio, and capital adequacy ratio collectively exert a significant influence on non performing financing in Islamic commercial banks. According to the partial test results (t-test), only the capital adequacy ratio demonstrates a negative and significant impact on non-performing financing. This implies that an increase in the capital adequacy ratio tends to reduce the non-performing financing ratio. The regression model interpretation suggests that all independent variables have a consistent relationship with the dependent variable. Therefore, an increase in the value of the capital buffer value, financing to funding ratio and capital adequacy ratio concurrently reduce the percentage of non-performing financing at Islamic commercial banks. The coefficient of determination indicates that the independent variables collectively explain 92.11% of the variation in the dependent variable. The remaining 7.89% is attributed to other variables not included in this study.